Роль межфазных границ в формировании градиентных структур в спеченных твердых сплавах - Лисовский, А.Ф. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The paper present the results of investigations into influence of interface boundaries on the
formation of gradient structures into cemented carbide articles. It is the theoretical basis for formation of different forms of gradient structures. The gradient structures are formed by using a treatment of an article with metal melts.